2018
DOI: 10.3389/fvets.2018.00323
|View full text |Cite
|
Sign up to set email alerts
|

Animal Welfare in Conservation Breeding: Applications and Challenges

Abstract: Animal welfare and conservation breeding have overlapping and compatible goals that are occasionally divergent. Efforts to improve enclosures, provide enriching experiences, and address behavioral and physical needs further the causes of animal welfare in all zoo settings. However, by mitigating stress, increasing behavioral competence, and enhancing reproduction, health, and survival, conservation breeding programs must also focus on preparing animals for release into the wild. Therefore, conservation breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 27 publications
0
59
0
2
Order By: Relevance
“…Zoo animal welfare is one of the key components in modern zoos achieving their aims (conservation, education, research and recreation). For example, with low welfare standards, an animal’s reproductive success decreases [ 7 , 8 ]. Godinez et al [ 9 ] also found that increases in animal stereotypies decreased visitor enjoyment, reducing the zoo’s opportunities to contribute towards both in situ and ex situ conservation strategies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zoo animal welfare is one of the key components in modern zoos achieving their aims (conservation, education, research and recreation). For example, with low welfare standards, an animal’s reproductive success decreases [ 7 , 8 ]. Godinez et al [ 9 ] also found that increases in animal stereotypies decreased visitor enjoyment, reducing the zoo’s opportunities to contribute towards both in situ and ex situ conservation strategies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…backpack attachment) [34,51], suggesting that the calling rate could also serve as a more general indicator of welfare [52]. Thus, we see no major obstacle in trying to generalize our approach to female zebra finches and other animals, including non-vocal learners [53,54].…”
Section: Discussionmentioning
confidence: 98%
“…Handling and housing animals in ways that minimize stress and exposing captive-bred animals to challenges that may prepare them for wild conditions are potential tools (Fraser, 2010). Overall improvements in captive conditions that promote the development of species-appropriate behaviors and reduce stress and disease can also contribute to effective conservation breeding programs (Greggor et al, 2018). It has also been encouraged to make released animals more comfortable in their release sites, based on the natal habitat preference induction phenomenon (Stamps and Swaisgood, 2007).…”
Section: Discussionmentioning
confidence: 99%